2019
DOI: 10.1016/j.cgh.2018.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Peroral Endoscopic Pyloromyotomy Reduces Symptoms, Increases Quality of Life, and Reduces Health Care Use For Patients With Gastroparesis

Abstract: In a retrospective study of patients who underwent GPOEM for refractory gastroparesis, we found the procedure significantly improved symptoms, increased quality of life, and reduced health care use related to gastroparesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(110 citation statements)
references
References 30 publications
(54 reference statements)
2
107
0
1
Order By: Relevance
“…Most of the reported studies originate from tertiary-care centres with endoscopic expertise and demonstrate 100% technical success. A recent study showed decline in ER visits and hospitalisation following G-POEM 155. The available data allow assessment of short-term efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the reported studies originate from tertiary-care centres with endoscopic expertise and demonstrate 100% technical success. A recent study showed decline in ER visits and hospitalisation following G-POEM 155. The available data allow assessment of short-term efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…). The technical success reached 100% coupled with significant symptomatic improvement as assessed by GCSI ( P < 0.0005), statistically significant reduction in hospitalization related to gastroparesis ( P = 0.0002), and improved quality of life ( P < 0.0005) . Moreover, Kahaleh et al .…”
Section: Evidence Through Literaturementioning
confidence: 96%
“…reported 13 patients who underwent G‐POEM for refractory gastroparesis (one diabetic, four idiopathic, and eight postsurgical) with clinical and GES improvement occurring in 73% and 67% respectively and GES normalization in 33% of patients . Mekaroonkamol et al . reported 30 patients with refractory gastroparesis who underwent G‐POEM (some patients reported by Mekaroonkamol et al .…”
Section: Evidence Through Literaturementioning
confidence: 99%
“…Gastric POEM first described by Khashab et al 28 in 2013 is fast becoming a treatment option for refractory gastroparesis especially for symptoms of nausea and vomiting. 29 Mekaroonkamol et al 29 compared refractory gastroparesis patients who underwent gastric POEM and those without, and they found the procedure significantly improved symptoms and quality of life, as well as reduced health care use related to gastroparesis.…”
Section: Future Of Gastroparesis In Asiamentioning
confidence: 99%